INDIUM TIN OXIDE MICRO-ELECTRODE ARRAY FOR NEURONAL STIMULTION AND RECORDING - Suthiwan Udomrat (2022)
Influence of applied electric field on biological cells has been widely investigated particularly for medical application, for example, to stimulate excitable neurons. Indium tin oxide (ITO), a transparent conducting semiconductor with biocompatible property, is used for electrical stimulating and electrochemical sensing the cell on the platform. In this work, ITO platform was developed by lithography micron-patterning and modified surface with protein coating. Surface morphology of the treated ITO surface was examined and biocompatibility was investigated by long period cell culture. SH-SY5Y, a human-neuroblastoma, was grown and subjected to 50 mV/ mm of steady state direct current electric field applying through the protein functionalized ITO platform for 30 min. The electrical treated cells exhibited morphological changes by extending neuronal processes length to 10. 75±30. 96 μm (n = 43) longer than the non-electrical treated cells. After electrical treatment, cell alignment following the electric field direction can also be observed. This work can demonstrate the biocompatibility and possibility use of treated ITO electrode for inducing cells morphological changes and controlling cell alignment. Furthermore, the fabricated ITO electrode can also demonstrate additional benefit of observing cellular activity by the means of electrical signal detection during the cellular progressions.